Ligand-based CAR-T cell: Different strategies to drive T cells in future new treatments - Ramírez-Chacón, Alejandro; Betriu-Méndez, Sergi; Bartoló-Ibars, Ariadna; González, Azucena; Martí, Mercè; Juan, Manel (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR)-based therapies are presented as innovative treatments for multiple malignancies. Despite their clinical success, there is scientific evidence of the limitations of these therapies mainly due to immunogenicity issues, toxicities associated with the infusion of the product, and relapses of the tumor. As a result, novel approaches are appearing aiming to solve and/or mitigate the harmful effects of CAR-T therapies. These include strategies based on the use of ligands as binding moieties or ligand-based CAR-T cells. Several proposals are currently under development, with some undergoing clinical trials to assess their potential benefits. In addition to these, therapies such as chimeric autoantibody receptor (CAAR), B-cell receptor antigen for reverse targeting (BAR), and even chimeric human leukocyte antigen (HLA) antibody receptor (CHAR) have emerged, benefiting from the advantages of antigenic ligands as antibody-binding motifs. This review focuses on the potential role that ligands can play in current and future antitumor treatments and in other types of diseases, such as autoimmune diseases or problems associated with transplantation.